TCPs: privileged scaffolds for identifying potent LSD1 inhibitors for cancer therapy. (May 2016) - Zheng, Yi-Chao; Yu, Bin; Chen, Zhe-Sheng; Liu, Ying; Liu, Hong-Min
Since the first lysine-specific demethylase (KDM), lysine-specific demethylase 1 (LSD1), was characterized in 2004, several families of KDMs have been identified. LSD1 can specifically demethylate H3K4me1/2, H3K9me1/2 as well as some nonhistone substrates. It has been demonstrated to be an oncogene as well as a drug target. Hence, tens of small-molecule LSD1 inhibitors have been designed, synthesized and applied for cancer treatment. However, the two LSD1 inhibitors that have been advanced into early phase clinical trials are trans-2-phenylcyclopropylamine (TCP) derivatives, which indicate that TCP is a druggable scaffold for LSD1 inhibitor. Here, we review the design, synthesis and properties of reported TCP-based LSD1 inhibitors as well as their biological roles.